Formation of components of economic security of the enterprise - Kobielieva, T. O.; Pererva, P. G.; Kopytsia, A. (Хмельницький національний університет, 2023)
It is suggested that the system of economic security of a construction enterprise should be understood as the interaction of the elements of activity, which allows the construction enterprise to work effectively by reducing the impact of threats. It has been proven that the economic security of a construction enterprise is characterized by complexity, the component of which is the presence of its components. In order to carry out a high-quality comprehensive assessment of the economic security of a construction enterprise, it is necessary to determine and substantiate its components.
Формування складових економічної безпеки підприємства
Keywords: economy, sustainable development, economic security, storage methods of formation